The Influence of Virtual Science Laboratory Design to Increase the Visual Literacy of Prospective Science Teachers - Adisti Yuliastrin; Mery Berlian; Alaniyah Syafaren (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Research that uses quasi-experimental methods to reveal the impact of using virtual laboratory media on visual literacy abilities. This research involved two groups, namely an experimental group that was exposed to virtual laboratory media, and a control group that received conventional learning. Both groups underwent a pretest and posttest to measure changes in visual literacy. This research design uses